2018
DOI: 10.1016/j.neurobiolaging.2017.11.005
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative EEG power and synchronization correlate with Alzheimer's disease CSF biomarkers

Abstract: Synaptic dysfunction is the best anatomical correlate of early cognitive impairment in Alzheimer's disease (AD). Electroencephalography (EEG) directly reflects brain electrical activity at the level of synapses. The aim of the present study was to investigate correlations of quantitative EEG measures, global field power (GFP) and global field synchronization (GFS), with conventional cerebrospinal fluid (CSF) biomarkers of neurodegeneration in patients diagnosed with subjective cognitive decline (n = 210), mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
105
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 60 publications
10
105
2
1
Order By: Relevance
“…where ␣-synuclein is invariable and amyloid-␤ very common, the frequency of epilepsy is extremely low The qEEG can be considered an indirect marker of neurodegeneration in AD [50]. In our study, the qEEG data were found to be substantially overlapping between AD-EPI and AD-CTR patients while, as a descriptive finding, interictal epileptiform discharges were more likely found in the AD-EPI group.…”
Section: Discussionsupporting
confidence: 43%
“…where ␣-synuclein is invariable and amyloid-␤ very common, the frequency of epilepsy is extremely low The qEEG can be considered an indirect marker of neurodegeneration in AD [50]. In our study, the qEEG data were found to be substantially overlapping between AD-EPI and AD-CTR patients while, as a descriptive finding, interictal epileptiform discharges were more likely found in the AD-EPI group.…”
Section: Discussionsupporting
confidence: 43%
“…Overall, quantitative EEG analysis provides the most direct and dynamic clinical representation of neuronal and synaptic function in AD patients; however, while it is sensitive to changes in neuronal circuit responses resulting from synaptic dysfunction, it cannot discriminate between the exact mechanisms of action underlying synaptic dys/function. Alterations in quantitative measures derived from EEG data in patients with AD have been widely described and have been shown to be sensitive to disease progression [134,138,139] and to correlate with CSF biomarkers of AD [140]. Furthermore, EEG is non-invasive, robust, efficacious, and widely available in hospitals.…”
Section: Biomarkers Of Synapse Damage or Lossmentioning
confidence: 99%
“…Another possible explanation would concur with the results obtained in other neurodegenerative diseases such as Alzheimer's; Lopez et al [65] found increased functional brain activity in anterior circuits using magnetoencephalography in mild cognitive impairment (an early condition in dementia). In [66], it was suggested that this hyperactivity may be one of the earliest dysfunctions of the pathophysiological process of neurodegeneration and would subsequently decline as dementia develops [67].…”
Section: Discussionmentioning
confidence: 99%